Method for using Cu composite small-size carbon nanospheres as multifunctional sensing material

By using small-size carbon nanospheres to support Cu nanocrystals, Cu composite small-size carbon nanospheres were prepared, which solved the problem of sensitivity reduction caused by Cu nanocrystal agglomeration, and achieved high sensitivity detection for a variety of substances, which was low cost and high specificity.

CN119897462APending Publication Date: 2025-04-29HARBIN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510081772.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, Cu nanocrystals in the field of biosensing face agglomeration problems, resulting in insufficient exposure of active sites and decreased sensitivity. At the same time, there is a lack of research on multifunctional sensing materials, making it difficult to detect multiple substances at the same time.

Method used

Small-size carbon nanospheres are used as the supporting material for Cu nanocrystals. Cu composite small-size carbon nanospheres are prepared through high-temperature decomposition and ultrasonic assisted methods to prevent Cu nanocrystals from agglomerating, improve their dispersion and sensitivity, and detect various substances.

Benefits of technology

Effectively prevent Cu nanocrystal agglomeration, improve the sensitivity of the sensor, and realize the detection of various substances of glucose, nitrite and formaldehyde, with low cost and significantly improved sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897462A_ABST
    Figure CN119897462A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing Cu composite small-size carbon nanospheres. The diameter of the prepared carbon nanospheres ranges from 300 nanometers to 400 nanometers, and the prepared carbon nanospheres have excellent monodispersity. The small-size carbon nanospheres are used as a supporting structure, the distance between interface Cu nanoparticles can be shortened, and therefore the signal intensity in the electrochemical sensing process is remarkably improved. In the aspect of glucose detection, the Cu composite small-size carbon nanospheres show higher sensitivity, the detection performance of the Cu composite small-size carbon nanospheres is obviously superior to that of pure Cu nanocrystals, and the enhancement coefficient can reach 1.38 times. In addition, the material has different potentials in glucose and formaldehyde detection, and shows excellent performance in nitrite detection in neutral electrolyte. According to the sensing material provided by the invention, the detection of multiple substances can be realized while the specificity is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal nanomaterial preparation and application, and in particular to a method of using Cu composite small-size carbon nanospheres as multifunctional sensing materials. Background Art

[0002] As eating habits evolve, unhealthy dietary choices and abuse of additives have led to the emergence of a variety of diseases. Diabetes is considered a serious global health problem. Therefore, it is essential to accurately and quickly monitor the glucose concentration in serum, food or beverages to maintain human health. As a typical food additive, the use of nitrite can maintain the color of meat. However, the association between excessive intake of nitrite and gastric cancer has been confirmed by many studies. Nitrite reacts with amines in the human body to form N-nitrosamines, a process that is considered to be a key factor in causing gastric cancer. Many studies have pointed out that when the nitrite content in drinking water exceeds 3 mg / L, it may have adverse effects on human health. Formaldehyde, as an important chemical product, is widely present in our daily lives. However, long-term exposure to low concentrations of formaldehyde may also cause impaired immune system, breathing difficulties and neurological problems. When people are exposed to formaldehyde environments with a concentration of more than 82 ppb for 30 minutes, they may experience symptoms such as nausea, vomiting, and sneezing. Therefore, in order to ensure human health, it is essential to efficiently, quickly and accurately detect the concentrations of nitrite, glucose and formaldehyde.

[0003] Among many sensor categories, electrochemical sensors have attracted much attention due to the changes in electrical signals generated by the interfacial catalytic oxidation process. They are popular for their fast response speed, excellent sensitivity and specificity. The performance of electrochemical sensors mainly depends on the electrode material. Commonly used electrode materials include precious metals such as Pt and Pd. However, these materials are expensive and are mainly used for the detection of a single substance. When two or more substances need to be detected simultaneously, the sensing electrode material must be replaced, which undoubtedly increases the complexity of the test. Therefore, it is of great scientific value to develop a cheap and multifunctional sensing material.

[0004] Metallic copper is one of the earliest metals used by humans. It has excellent ductility, conductivity and catalytic properties. Nanoscale copper is considered to be a very promising electrochemical sensor electrode material due to its excellent stability and biocompatibility, as well as its relatively low cost. Nevertheless, the application of copper-based nanomaterials in the field of biosensing still faces some challenges:

[0005] 1. Although small-sized Cu nanocrystals have high active sites, they are poorly dispersed and easily agglomerated, which limits the effective exposure of their active sites. When the specific surface area decreases, the sensitivity of Cu nanocrystals as sensing materials will decrease significantly.

[0006] 2. In order to ensure the specificity of the detection process (i.e., anti-interference ability), most Cu-based sensors are designed only for a single substance. Currently, there are relatively few studies on the construction of multifunctional Cu-based sensing materials.

[0007] Using carbon-based materials (such as carbon nanotubes and graphene) as supporting structures can significantly improve the monodispersity of nanomaterials. However, the preparation process of traditional carbon supporting materials (such as carbon nanotubes and graphene) is relatively complicated and requires strict control of synthesis conditions (including factors such as temperature, pressure and solvent), which brings high safety risks to large-scale production.

[0008] In previous studies, the inventors proposed a method for preparing carbon nanospheres modified by Cu and demonstrated their application in catalytic dye degradation (CN202410346512.7). However, the carbon-based support material provided is large in size (about 2 microns in diameter), and the large structure leads to an increase in the distance between individual Cu nanoparticles, which is not conducive to the transmission of interfacial charges, so the resulting material cannot be used as a high-performance sensing material. Summary of the invention

[0009] The present invention aims at the problems existing in the prior art background and provides a method for preparing Cu composite small-sized carbon nanospheres.

[0010] Small-sized carbon nanospheres are used as supporting materials for Cu nanocrystals. They can effectively prevent the agglomeration of Cu nanocrystals, thereby maintaining their high active sites. At the same time, small-sized carbon nanospheres can also provide additional electron transmission channels during the electrochemical sensing process, further improving the sensitivity of the sensor. Example applications show that the use of Cu-composite small-sized carbon nanospheres as multi-energy sensing materials can effectively detect the concentrations of nitrite, glucose, and formaldehyde.

[0011] The proposed method for preparing Cu-composite small-sized carbon nanospheres has the following specific steps:

[0012] 1. Using deionized water as solvent, prepare a hydrochloric acid solution of a certain concentration (concentration is 0.015-0.02 mol / L), recorded as solution 1;

[0013] 2. Use ethanol as solvent to prepare a certain concentration of KOH solution (0.045-0.048 g / mL), stir evenly, and record it as solution 2;

[0014] 3. Add ascorbic acid (AA) and polyvinyl pyrrolidone (PVP) to the prepared hydrochloric acid solution in proportion, stir again, and heat at 120°C for 8 hours, which is recorded as reaction solution 1, wherein the mass of AA added per milliliter of hydrochloric acid solution is 0.013-0.014 g, and the mass of PVP added per milliliter of hydrochloric acid solution is 0.0009-0.0010 g;

[0015] 4. After the reaction solution 1 is heated, it is cooled naturally, mixed with solution 2, and subjected to ultrasonic reaction for 30 minutes. The resulting mixed solution is recorded as mixed solution 3;

[0016] 5. Using deionized water as solvent, prepare a NaBH4 solution (31-32 mg / mL) of a certain concentration, and add it to the mixed solution 3 in proportion, recorded as mixed solution 4, wherein the volume ratio of NaBH4 to mixed solution 3 is 40:173;

[0017] 6. Using deionized water as solvent, prepare CuCl2 with a concentration of 20-21 mg / mL, and add it dropwise into the mixed solution 4 4 times according to the volume ratio. The time interval between each addition is 1 minute. After the addition is completed, ultrasonic reaction is carried out at 40°C for 20 minutes. Among them, the volume ratio of the mixed solution 4 to the CuCl2 aqueous solution is in the range of 14:1-13:1.

[0018] 7. After the reaction is completed, the reaction solution and the product are separated by centrifugation, the precipitate is washed 1-3 times with deionized water and ethanol, and then centrifuged again, the powder is extracted and dried at 45-60°C for 12 hours.

[0019] In the above preparation process, AA is decomposed into carbon element at high temperature, and small-sized carbon nanospheres are formed under the action of PVP; at room temperature, CuCl2 generates Cu element under the action of strong reducing agent NaBH4, and under the assistance of ultrasonic wave, Cu element is generated and evenly dispersed on the surface of small-sized carbon nanospheres.

[0020] In addition, the present invention also discloses a method for detecting the concentration of glucose, nitrite and formaldehyde solution by using Cu composite small-sized carbon nanospheres. The specific detection method is as follows:

[0021] 1. Use Cu composite small-size carbon nanospheres to modify the working electrode, Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0022] 2. Select appropriate electrolyte, set working potential, and measure the timing response current curve of glucose / nitrite / formaldehyde solution at different concentrations. The nitrite electrolyte is 0.01 mol / L phosphate buffered saline (PBS buffer), the electrolyte for glucose sensing is 1 mol / L KOH, and the electrolyte for formaldehyde sensing is 0.1 mol / L KOH.

[0023] 3. Fitting functions based on the collected electrical signal data and the corresponding glucose / nitrite / formaldehyde solution concentrations;

[0024] 4. Place the three-electrode system in the solution to be tested, measure the timing response current curve, record the response current signal data, and calculate the concentration of the glucose / nitrite / formaldehyde solution in the test substance according to the fitting function in step 3.

[0025] By adopting the method of the present invention, the following positive effects can be achieved:

[0026] 1. The morphology of carbon support materials was optimized.

[0027] The present invention provides a method for preparing Cu composite small-sized carbon nanospheres, wherein the prepared carbon nanospheres have a diameter between 300 and 400 nanometers and have excellent dispersibility. As a supporting structure, these small-sized carbon nanospheres can shorten the distance between interface Cu nanoparticles, thereby helping to improve the signal strength during electrochemical testing.

[0028] 2. The sensitivity of the sensor was successfully improved without increasing the cost of the sensing material.

[0029] As a sensing material, the cost of Cu composite small-sized carbon nanospheres is lower than that of pure Cu nanocrystals, which effectively reduces the cost of sensing materials. When detecting glucose concentration, Cu composite small-sized carbon nanospheres have higher sensitivity, significantly surpassing pure Cu nanocrystals, and the enhancement coefficient can reach 1.38.

[0030] 3. The prepared Cu-composite small-sized carbon nanospheres can realize the detection of a variety of substances.

[0031] In the present invention, Cu composite small-size carbon nanospheres can detect the concentration of formaldehyde and glucose solutions in an alkaline environment, while in a neutral solution (using PBS buffer as an electrolyte), Cu composite small-size carbon nanospheres can detect nitrite. Due to the difference in the electrocatalytic oxidation potential of glucose and formaldehyde, this ensures that the sensor will not produce signal interference when detecting the concentration of glucose and formaldehyde. The detection of sodium nitrite needs to be carried out in a neutral environment. In contrast, glucose and formaldehyde solutions can hardly detect electrical signals in a neutral electrolyte. Even if the solution contains glucose and formaldehyde, it will not interfere with the detection of nitrite. Therefore, the sensing material provided by the present invention can achieve the detection of multiple substances (glucose / formaldehyde / sodium nitrite) while maintaining specificity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the X-ray diffraction pattern of the sample obtained in Example 1 of the present invention.

[0033] Figure 2 This is a field emission scanning electron microscope image of the sample obtained in Example 1 of the present invention.

[0034] Figure 3 This is the chronoamperometric curve of the sensor constructed in Application Example 1 of the present invention in glucose solutions of different concentrations.

[0035] Figure 4 It is the fitting equation between the glucose solution concentration and the response current density in the sensor constructed in Application Example 1 of the present invention.

[0036] Figure 5 This is the chronoamperometric curve of the sensor constructed in Application Example 2 of the present invention in nitrite solutions of different concentrations.

[0037] Figure 6 It is the fitting linear equation between the nitrite concentration and the response current density in the sensor constructed in the second application example of the present invention.

[0038] Figure 7 This is the chronoamperometric curve of the sensor constructed in Application Example 3 of the present invention in formaldehyde solutions of different concentrations.

[0039] Figure 8 It is the fitting linear equation between the formaldehyde solution concentration and the response current density in the sensor constructed in Application Example 3 of the present invention.

[0040] Fig. 9 It is a schematic diagram of the operation of detecting glucose, nitrite and formaldehyde by using Cu composite small-sized carbon nanospheres as multifunctional sensing materials in the present invention.

[0041] Fig.10 This is a field emission scanning electron microscope picture of the product obtained in comparative example 1 of the present invention.

[0042] Fig.11 This is a field emission scanning electron microscope picture of the product obtained in Comparative Example 2 of the present invention.

[0043] Fig.12 It is the fitting equation between the glucose solution concentration and the response current density in the sensor constructed in Comparative Example 3 of the present invention.

[0044] Fig.13 It is the fitting linear equation between the nitrite concentration and the response current density in the sensor constructed in comparative example 4 of the present invention.

[0045] Fig.14 It is the fitting linear equation between the formaldehyde solution concentration and the response current density in the sensor constructed in Comparative Example 5 of the present invention.

[0046] Fig.15 This is the X-ray diffraction pattern of the sample obtained in Comparative Example 6 of the present invention.

[0047] Fig.16 It is the fitting equation between the glucose solution concentration and the response current density in the sensor constructed in Comparative Example 7 of the present invention.

[0048] Fig.17 It is the fitting linear equation between the nitrite concentration and the response current density in the sensor constructed in comparative example eight of the present invention.

[0049] Fig.18 It is the fitting linear equation between the formaldehyde solution concentration and the response current density in the sensor constructed in Comparative Example 9 of the present invention. DETAILED DESCRIPTION

[0050] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0051] Example 1: Preparation of Cu-composite small-sized carbon nanospheres

[0052] 1. Use deionized water as solvent to prepare 53mL of 0.019mol / L hydrochloric acid solution;

[0053] 2. Use ethanol as solvent to prepare 120 mL of 0.046 g / mL KOH solution, stir evenly, and record it as solution 2;

[0054] 3. Add 0.7 g of AA and 0.05 g of PVP to the prepared hydrochloric acid solution, stir again and place in a reactor and heat at 120°C for 8 hours, which is recorded as reaction solution 1;

[0055] 4. After the reaction of reaction solution 1 is completed, it is cooled naturally, and reaction solution 1 is added into solution 2 for mixing, and ultrasonic reaction is performed for 30 minutes to obtain mixed solution 3;

[0056] 5. Use deionized water as solvent to prepare 40 mL of 31.2 mg / mL NaBH4 solution, add it to mixed solution 3, and record it as mixed solution 4;

[0057] 6. Use deionized water as solvent, prepare 16mL of CuCl2 with a concentration of 20.6mg / mL, and add it dropwise to the mixed solution 4 in 4 times, with an interval of 1 minute between each addition. After the addition is completed, ultrasonically react at 40℃ for 20 minutes.

[0058] 7. After the reaction is completed, the reaction solution and the product are separated by centrifugation, and the precipitate is washed 1 to 3 times with deionized water and ethanol, and then centrifuged again to extract the powder, which is then dried at 50°C for 12 hours.

[0059] In order to analyze the composition of the product, we conducted an X-ray diffraction test on the obtained samples. The results are as follows Figure 1 As shown in the figure, it can be observed that the X-ray diffraction peaks of the obtained sample are consistent with the corresponding positions of the Cu standard diffraction JCPDS card (89-2838).

[0060] In order to explore the morphology of the obtained product, we measured the field emission scanning electron microscope of the sample obtained in Example 1, as shown in the attached manual. Figure 2 As shown, the obtained sample is a spherical structure, and its surface exposes small nanoparticles. In order to study the element distribution of the sample, we conducted energy dispersive X-ray spectroscopy test on the obtained sample, and the study showed that the spherical structure is C material, and the particles on its surface are Cu single substance. Therefore, it can be seen that Cu composite small-sized carbon nanospheres can be successfully prepared according to the steps of Example 1.

[0061] Compared with the traditional Cu nanoparticle accumulation phenomenon, the present invention uses small-sized carbon nanospheres as the carrier of carbon materials. This method not only avoids the use of Cu single-substance nanoparticles, but also effectively prevents the aggregation of Cu single-substance nanocrystals. This method increases the actual specific surface area, making the final product a sensing material with excellent performance.

[0062] Application Example 1: Using Cu-composite small-sized carbon nanospheres as glucose concentration sensing materials

[0063] The Cu composite small-size carbon nanospheres involved in the present invention can be used to detect the concentration of glucose solution. The specific detection method is as follows:

[0064] 1. The working electrode was modified by using Cu composite small-size carbon nanospheres (using ethanol as solvent to prepare a suspension with a concentration of 2 mg / mL of the product obtained in Example 1, and a volume of 6 μL of the suspension was dripped on the glassy carbon working electrode. After the liquid evaporated, a volume of 6 μL of a 0.05% perfluorosulfonic acid polymer solution was dripped. After the liquid evaporated, the modification was completed), Ag / AgCl was used as the reference electrode, and the Pt wire electrode was used as the counter electrode, and connected to the electrochemical workstation;

[0065] 2. Using 1 mol / L KOH as the electrolyte, add a certain amount of glucose solution to the solution every 100 seconds to achieve a gradient increase in the glucose concentration in the solution, increasing by 5 mmol / L each time until it reaches 105 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 1.2 V vs Ag / AgCl;

[0066] 3. Fitting a function based on the measured electrical signal data and the corresponding glucose concentration;

[0067] 4. Place the three-electrode system in the solution to be tested (alkaline solution environment), measure its timing response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0068] like Figure 3 As shown in the figure, with the increase of glucose concentration, the response current density signal increases linearly and tends to be stable in a very short time. The change of the response electrical signal is due to the electrocatalytic oxidation of glucose by Cu composite small-sized carbon nanospheres.

[0069] like Figure 4 The response current density is linearly related to the concentration of glucose solution, and the fitting function is Y=416.58X+1109.61. Among them, the Y value corresponds to the response current density, and X is the glucose solution. The linear concentration range is 0-100mmol / L.

[0070] When testing the substance to be tested, the response current density at a potential of 1.2 V is used as the Y value, which is substituted into the fitting function, and the obtained X value is the concentration of the glucose to be tested.

[0071] Application Example 2: Using Cu-composite small-sized carbon nanospheres as nitrite concentration sensing material

[0072] The Cu composite small-sized carbon nanospheres obtained by the present invention can detect the concentration of nitrite solution, and the specific detection method is as follows:

[0073] 1. Use Cu composite small-size carbon nanospheres to modify the working electrode (modification method is the same as application example 1), Ag / AgCl as the reference electrode, Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0074] 2. Use PBS with a concentration of 0.01 mol / L as the electrolyte, add a certain amount of sodium nitrite solution to the solution every 100 seconds, so that the concentration of sodium nitrite in the solution increases by a gradient of 5 mmol / L each time until it reaches 125 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 1.3 V vs Ag / AgCl;

[0075] 3. Fitting function based on measured electrical signal data and corresponding sodium nitrite concentration;

[0076] 4. Place the three-electrode system in the solution to be tested (neutral solution environment), measure its timing response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0077] like Figure 5 As shown: nitrite is oxidized at a potential of 1.3 V. As the concentration of nitrite in the solution increases, the response current density increases linearly, and the linear range can reach 0-125 mmol / L.

[0078] like Figure 6 The response current density is linearly related to the concentration of nitrite solution, and the fitting function is Y=120.94X+325.78, where the Y value corresponds to the response current density and X is the nitrite solution.

[0079] When testing the substance to be tested, the response current density at a potential of 1.3 V is used as the Y value, which is substituted into the fitting function, and the obtained X value is the concentration of the substance to be tested, sodium nitrite.

[0080] Application Example 3: Using Cu-composite small-sized carbon nanospheres as formaldehyde concentration sensing material

[0081] The Cu composite small-sized carbon nanospheres obtained by the present invention can detect the concentration of formaldehyde solution, and the specific detection method is as follows:

[0082] 1. Use Cu composite small-size carbon nanospheres to modify the working electrode (modification method is the same as application example 1), Ag / AgCl as the reference electrode, Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0083] 2. Use 0.1 mol / L KOH as the electrolyte, add a certain amount of formaldehyde solution to the solution every 100 seconds, so that the formaldehyde concentration in the solution increases by 1 mmol / L each time until it reaches 26 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 0.75 V vsAg / AgCl;

[0084] 3. Fitting function based on measured electrical signal data and corresponding formaldehyde concentration;

[0085] 4. Place the three-electrode system in the solution to be tested (alkaline solution environment), measure its timing response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0086] like Figure 7 As shown, formaldehyde is oxidized under a potential of 0.75 V. As the concentration of formaldehyde in the solution increases, the response current density increases linearly, and the linear range can reach 0-26 mmol / L.

[0087] like Figure 8 The response current density is linearly related to the concentration of formaldehyde solution, and the fitting function is Y=110.02X+42.30, where the Y value corresponds to the response current density and X is the concentration of formaldehyde solution.

[0088] When testing the substance to be tested, the response current density at a potential of 0.75 V is used as the Y value, which is substituted into the fitting function. The calculated X value represents the concentration of formaldehyde in the substance to be tested.

[0089] In the present invention, since there is a significant difference in the working potentials of glucose and formaldehyde sensors, the provided sensing material can simultaneously detect the concentrations of glucose and formaldehyde solutions.

[0090] In order to more intuitively present the detailed operation process of this patent in determining the concentrations of glucose, sodium nitrite and formaldehyde, we have integrated these steps into a technical flow chart, see Fig. 9 .

[0091] Comparative Example 1: Preparation of small-sized carbon nanospheres

[0092] In order to compare the difference in sensing performance between the material obtained in the embodiment of the present invention and the material consisting only of small-sized carbon nanospheres, we prepared pure carbon nanospheres according to the following steps:

[0093] 1. Use deionized water as solvent to prepare 53mL of 0.019mol / L hydrochloric acid solution;

[0094] 2. Add 0.7 g of AA and 0.05 g of PVP to the prepared hydrochloric acid solution, stir again and heat at 120°C for 8 hours, which is recorded as reaction solution 1;

[0095] 3. After the reaction is completed, the reaction solution and the product are centrifuged, the precipitate is washed 1 to 3 times with deionized water and ethanol, and then centrifuged again, the powder is extracted and dried at 50°C for 12 hours.

[0096] In order to explore the composition of the sample obtained in comparative example 1, we conducted an energy dispersive X-ray spectroscopy (EDS) test on the obtained sample. Among them, the atomic percentage of C element accounts for more than 78.45%. In addition, the X-ray diffraction spectrum shows that the sample obtained in the comparative example is amorphous carbon.

[0097] In order to explore the morphology of the powder in comparative example 1, we conducted a scanning electron microscope test on it. The results are as follows: Fig.10 As shown. Fig.10 It can be seen that the obtained carbon nanomaterial is a regularly arranged sphere with a diameter of 300-400nm.

[0098] Comparative Example 2: Preparation of carbon nanospheres of other sizes (key parameter - the effect of PVP on obtaining small-sized carbon nanospheres)

[0099] As a surfactant, PVP is used to improve the surface properties of nanomaterials. In the present invention, the addition of PVP plays a crucial role in obtaining small-sized carbon nanospheres, which helps to improve the dispersibility of carbon nanospheres. In order to verify this point of view, we carried out comparative example 2, and the specific preparation steps are as follows:

[0100] 1. Use deionized water as solvent to prepare 53mL of 0.019mol / L hydrochloric acid solution;

[0101] 2. Add 0.7 g of AA to the prepared hydrochloric acid solution, stir again and heat at 120°C for 8 hours, which is recorded as reaction solution 1;

[0102] 3. The reaction solution was centrifuged, and the precipitate was washed 1 to 3 times with deionized water and ethanol, and then centrifuged again, and the powder was extracted and dried at 45° C. for 12 hours.

[0103] Compared with comparative example 1, comparative example 2 does not add PVP. Fig.11 As shown, it can be seen that the generated C particles do not reach the nanometer level, and the dispersion and uniformity are poor, with a diameter of 1-2 microns.

[0104] In summary, adding an appropriate concentration of PVP is one of the key parameters for obtaining small-sized carbon nanospheres in the present invention. PVP mainly plays a role of steric hindrance and end-capping in the reaction process. During the formation of carbon nanoparticles, PVP molecules will be adsorbed on the surface of carbon nanoparticles to form a layer of polymer protective film. This protective film increases the distance between particles, making it difficult for particles to agglomerate with each other, thereby limiting the growth size of carbon nanospheres. It is worth noting that excessive use of PVP will inhibit the formation of C nanospheres, making it difficult to obtain the target product.

[0105] Comparative Example 3: Detection of Glucose Solution Concentration by Small-Sized Carbon Nanospheres (Sample Obtained from Comparative Example 1)

[0106] 1. Use small-sized carbon nanospheres to modify the working electrode (the method is the same as the application example), Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0107] 2. Use 1 mol / L KOH as the electrolyte, and add a specific amount of glucose solution to the solution every 100 seconds to increase the concentration of glucose in the solution by 5 mmol / L each time until it reaches 105 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 1.2 V vsAg / AgCl;

[0108] 3. Fitting a function based on the measured electrical signal data and the corresponding glucose concentration;

[0109] 4. Place the three-electrode system in the solution to be tested (alkaline solution environment), measure the timed response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0110] According to the fitting curve, Fig.12 The response current density shows a linear functional relationship with the glucose concentration. Fig.12 It can be seen that the small-sized carbon nanospheres obtained in Comparative Example 1 can hardly detect the glucose concentration.

[0111] Comparative Example 4: Detection of nitrite solution concentration by small-sized carbon nanospheres (sample obtained in Comparative Example 1)

[0112] 1. Use small-sized carbon nanospheres to modify the working electrode (the method is the same as the application example), Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0113] 2. Use PBS with a concentration of 0.01 mol / L as the electrolyte, and add a certain amount of sodium nitrite solution to the solution every 100 seconds, so that the concentration of sodium nitrite in the solution increases by a gradient of 5 mmol / L each time. During this process, measure and record the chronoamperometric curve at a constant potential of 1.3 V vs Ag / AgCl;

[0114] 3. Fitting function based on measured electrical signal data and corresponding sodium nitrite concentration;

[0115] 4. Place the three-electrode system in the solution to be tested (neutral solution environment), measure the timed response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0116] According to the fitting curve, Fig.13The linear relationship between the response current density and the nitrite concentration is shown. Fig.13 It can be seen that from the beginning of the nitrite concentration in the electrolyte being 0 to the concentration reaching 125 mmol / L, the response current density does not change substantially, from which it can be concluded that the small-sized carbon nanospheres obtained in comparative example 1 have no nitrite sensing performance.

[0117] Comparative Example 5: Detection of formaldehyde solution concentration by small-sized carbon nanospheres (sample obtained in Comparative Example 1)

[0118] 1. Use small-sized carbon nanospheres to modify the working electrode (the method is the same as the application example), Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0119] 2. Using KOH with a concentration of 0.1 mol / L as the electrolyte, add a specific amount of formaldehyde solution to the solution every 100 seconds so that the concentration of formaldehyde in the solution increases by 1 mmol / L each time until it reaches 26 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 0.75 V vs Ag / AgCl;

[0120] 3. Fitting function based on measured electrical signal data and corresponding formaldehyde concentration;

[0121] 4. Place the three-electrode system in the solution to be tested (alkaline solution environment), measure the timed response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0122] According to the fitting curve, Fig.14 The linear relationship between the response current density and the formaldehyde concentration is shown. Fig.14 It can be seen that as formaldehyde is gradually added until 26mmol / L, the response current density remains basically unchanged. It can be inferred that the small-sized carbon nanospheres in Comparative Example 1 have almost negligible formaldehyde sensing performance.

[0123] Comparative Example 6: Preparation of Pure Cu Nanocrystals

[0124] The present invention modifies the metal Cu on the surface of small-sized carbon nanospheres by an in-situ deposition method, and the carbon nanospheres are used as supporting materials to prevent the aggregation of Cu particles.

[0125] In order to compare the difference in sensing performance between the material obtained in the embodiment of the present invention and Cu single substance nanocrystals, we prepared pure Cu nanocrystals according to the following steps. The specific steps are as follows:

[0126] 1. Use ethanol as solvent to prepare 120 mL of 0.046 g / mL KOH solution, stir evenly, and record it as mixed solution 1;

[0127] 2. Use deionized water as solvent to prepare 40 mL of 31.2 mg / mL NaBH4 solution, add it into mixed solution 1 in proportion, and record it as solution 2;

[0128] 3. Use deionized water as solvent, prepare 16mL of CuCl2 with a concentration of 20.6mg / mL, and add it dropwise into mixed solution 2 in 4 times, with an interval of 1 minute between each addition. After the addition is completed, ultrasonically react at 40℃ for 20 minutes.

[0129] 4. After the reaction is completed, the reaction solution is centrifuged, and the precipitate is washed 1 to 3 times with deionized water and ethanol, and then centrifuged again, and the powder is extracted and dried at 50°C for 12 hours.

[0130] In order to analyze the composition of the product, we conducted an X-ray diffraction test on the obtained samples. The results are as follows Fig.15 As shown in the figure, it can be observed that the diffraction peak position of the X-ray diffraction pattern of the obtained sample matches the Cu standard diffraction JCPDS card (89-2838). In addition, no characteristic peaks of other substances such as Cu2O or CuO were detected in the product. This indicates that the obtained product is Cu single substance nanocrystals.

[0131] Comparative Example 7: Detection of Glucose Solution Concentration by Cu Nanocrystals (Sample Obtained in Comparative Example 6)

[0132] 1. Use Cu nanocrystals to modify the working electrode (the modification method is the same as the application example), Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0133] 2. Use 1 mol / L KOH as the electrolyte, and add a specific amount of glucose solution to the solution every 100 seconds to increase the concentration of glucose in the solution by 5 mmol / L each time until it reaches 105 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 1.2 V vsAg / AgCl;

[0134] 3. Fitting a function based on the measured electrical signal data and the corresponding glucose concentration;

[0135] 4. Place the three-electrode system in the solution to be tested (alkaline environment), measure the timed response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0136] like Fig.16As shown, under the action of the sample (Cu nanocrystal) obtained in comparative example 6, the response current density is linearly related to the concentration of the glucose solution, the fitting function is Y=196.91X+577.70, and the corresponding slope (sensitivity) of the linear equation is 196.91μA / mM·cm 2 In comparison, the sensitivity of the sensing material of Example 1 of this patent to glucose detection is 416.58μA / mM·cm 2 , which is 2.11 times more sensitive than Cu nanocrystals. Therefore, it can be seen that the product obtained in Example 1 is helpful for more accurate detection of the glucose concentration of the object to be detected when used as a sensing material.

[0137] The excellent sensing properties of the sample obtained in Example 1 are due to two reasons: 1) small-sized carbon nanoparticles as supporting materials are conducive to the dispersion of Cu nanocrystals and increase the specific surface area; 2) the carbon material itself has a very strong adsorption capacity and is easy to adsorb electroactive substances during the electrocatalytic oxidation of glucose, thereby accelerating the process of glucose sensing.

[0138] Comparative Example 8: Detection of the concentration of nitrite solution by Cu nanocrystals (sample obtained in Comparative Example 6)

[0139] 1. Use Cu nanocrystals to modify the working electrode (the method is the same as the application example), Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0140] 2. Using PBS with a concentration of 0.01 mol / L as the electrolyte, add a specific amount of sodium nitrite solution to the solution every 100 seconds, so that the concentration of sodium nitrite in the solution increases by 5 mmol / L each time until it increases linearly to 125 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 1.3 V vs Ag / AgCl;

[0141] 3. Fitting function based on measured electrical signal data and corresponding sodium nitrite concentration;

[0142] 4. Place the three-electrode system in the solution to be tested (neutral solution environment), measure the timed response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0143] like Fig.17 As shown, the fitting equation of the response current density and sodium nitrite concentration is Y=34.66X+17.56, and the sensitivity is 34.66μA / mM·cm 2 .

[0144] Compared with the sensitivity of sodium nitrite detection in the second application example of this patent (120.94μA / mM·cm 2) compared to the pure Cu nanocrystals, the sensitivity to sodium nitrite is only 28.7% of that of the second application example of the present invention. This indicates that the Cu composite small-sized carbon nanospheres provided by the present invention have a more superior sensing performance to nitrite.

[0145] Comparative Example 9: Detection of the concentration of formaldehyde solution by Cu nanocrystals (sample obtained in Comparative Example 6)

[0146] 1. Use Cu nanocrystals to modify the working electrode (the method is the same as the application example), Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, and connect to the electrochemical workstation;

[0147] 2. Use 0.1 mol / L KOH as the electrolyte, add a certain amount of formaldehyde solution to the solution every 100 seconds, and ensure that the concentration of formaldehyde in the solution increases linearly by 1 mmol / L each time until it reaches 17 mmol / L. During this process, measure and record the chronoamperometric curve at a constant potential of 0.75 V vs Ag / AgCl;

[0148] 3. Fitting function based on measured electrical signal data and corresponding formaldehyde concentration;

[0149] 4. Place the three-electrode system in the solution to be tested (alkaline solution environment), measure the timed response current curve, record the response current signal, and calculate the concentration of the substance to be tested according to the fitting function in step 3.

[0150] like Fig.18 As shown, the fitting equation of the response current density and formaldehyde concentration is Y = 35.91X + 0.99, and the sensitivity is 35.91 μA / mM·cm 2 .

[0151] According to the sensitivity of formaldehyde detection in the third application example of this patent (110.02μA / mM·cm 2 ) shows that the sensitivity enhancement factor of Cu composite small-sized carbon nanospheres compared with Cu nanocrystals can reach 3.06. This proves that the Cu composite small-sized carbon nanospheres provided by the present invention exhibit more excellent sensing performance for formaldehyde.

[0152] In summary, this article provides a method for preparing Cu composite small-sized carbon nanospheres and uses them for detecting the concentration of various substances. It should be noted that the above is a preferred embodiment of the invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for using Cu composite small-size carbon nanospheres as multifunctional sensing materials, characterized in that: The preparation method of Cu-composite small-sized carbon nanospheres is as follows: (1) Using deionized water as solvent, prepare a hydrochloric acid solution with a concentration of 0.015-0.02 mol / L, referred to as solution 1; (2) Using ethanol as solvent, prepare a KOH solution with a concentration of 0.045-0.048 g / mL and stir evenly, which is referred to as solution 2; (3) Add ascorbic acid and polyvinyl pyrrolidone to the prepared hydrochloric acid solution in proportion, stir again, and heat at 120° C. for 8 hours, which is referred to as reaction solution 1; (4) After the reaction of reaction solution 1 is completed, it is naturally cooled, and reaction solution 1 is added to solution 2 for mixing, and ultrasonic reaction is performed for 30 minutes to obtain mixed solution 3; (5) Using deionized water as solvent, prepare a NaBH4 solution of a certain concentration, and add it to the mixed solution 3 in proportion, which is recorded as the mixed solution 4; (6) Using deionized water as solvent, prepare CuCl2 with a concentration of 20-21 mg / mL, and add it dropwise to the mixed solution 4 4 times according to the volume ratio, with the interval between each addition being 1 minute, and then ultrasonically react at 40° C. for 20 minutes after the addition is completed; (7) After the reaction is completed, the reaction solution and the product are separated by centrifugation, the precipitate is washed 1 to 3 times with deionized water and ethanol, and then centrifuged again to extract the powder, which is then dried at 45-60° C. for 12 hours; In step (3), the mass of ascorbic acid added per milliliter of hydrochloric acid solution is in the range of 0.013-0.014 g, and the mass of polyvinyl pyrrolidone added per milliliter of hydrochloric acid solution is in the range of 0.0009-0.0010 g; In step (5), the concentration of the NaBH4 aqueous solution is in the range of 31-32 mg / mL, and the volume ratio of NaBH4 to the mixed solution 3 is 40:173; In step (7), the volume ratio of the mixed solution 4 to the CuCl2 aqueous solution is in the range of 14:1-13:

1.

2. A Cu composite small-size carbon nanosphere, characterized in that: Obtained by the preparation method described in claim 1.

3. A method for using Cu composite small-sized carbon nanospheres as multifunctional sensing materials, characterized in that: The method for detecting the concentration of glucose, nitrite and formaldehyde solution using Cu composite small-sized carbon nanospheres is as follows: (1) Using Cu composite small-size carbon nanospheres to modify the working electrode, Ag / AgCl as the reference electrode, and Pt wire electrode as the counter electrode, connected to an electrochemical workstation; (2) selecting a suitable electrolyte, setting the working potential, and measuring the chrono-response current curves of glucose concentration / nitrite / formaldehyde solution at different concentrations; (3) fitting a function based on the collected electrical signal data and the corresponding glucose / nitrite / formaldehyde solution concentrations; (4) placing the three-electrode system in the test solution, measuring the timed response current curve, recording the response current signal data, and calculating the concentration of the glucose / nitrite / formaldehyde solution in the test substance according to the function fitted in step (3); In step (2), the electrolyte selected for nitrite sensing is 0.01 mol / L phosphate buffered saline, the electrolyte selected for glucose sensing is 1 mol / L KOH, and the electrolyte selected for formaldehyde sensing is 0.1 mol / L KOH.

Citation Information

Patent Citations

  • Method for enhancing catalytic degradation of organic dye by using Cu-modified C nanospheres

    CN118255444A